Potential Explanatory Factors for the Concurrent Experience of Dyspnea and Pain in Patients with COPD. Issue 1 (31st December 2022) - Bartz-Overman, Colin; Albanese, Anita M.; Fan, Vincent; Locke, Emily R.; Parikh, Toral; Thielke, Stephen
Abstract: Previous research has identified unexpectedly strong associations between dyspnea and pain, but the reasons remain unclear. Ascertaining the underlying biological and psychological mechanisms might enhance the understanding of the experience of both conditions, and suggest novel treatments. We sought to elucidate whether demographic factors, disease severity, psychological symptoms and biomarkers might account for the association between pain and dyspnea in individuals with COPD. We analyzed data from 301 patients with COPD who were followed in a prospective longitudinal observational study over 2 years. Measures included self-reported dyspnea and pain, pulmonary function tests, serum levels of inflammatory cytokines, measures of physical deconditioning, and scales for depression and anxiety. Analyses involved cross-sectional and longitudinal linear regression models. Pain and dyspnea were strongly correlated cross-sectionally ( r  = 0.77, 95% CI 0.72–0.82) and simultaneously across time ( r  = 0.42, 95% CI 0.28–0.56). Accounting for any of the other health factors only slightly mitigated the associations. Symptoms of pain and dyspnea thus may be fundamentally linked in COPD, rather than being mediated by common biological, psychological, or functional factors. From the patient's perspective, pain and dyspnea may be part of the same essential experience. It is possible that treatments for one condition would improve the other.